The efficacy and safety of sodium nitroprusside in the treatment of schizophrenia: a meta-analysis - Fei, Xinxing; Li, Jiyang; Wang, Shiqi; Wang, Jianxiong; Guo, Changmei; Qisha, Rizhi; Gao, Yaqian; Hu, Yue (Frontiers in Psychiatry, 2023)
Objective: Schizophrenia is a serious mental disease that brings not only serious burdens to patients and their families but also serious challenges to society. More research is needed to find better drugs to treat schizophrenia. This meta-analysis investigated the efficacy and safety of sodium nitroprusside in the treatment of schizophrenia.Methods: Randomized controlled trials comparing the efficacy and safety of sodium nitroprusside in the treatment of schizophrenia were searched via English and Chinese databases. The outcomes, including the Positive and Negative Syndrome Scale (PANSS) and Brief Psychiatric Rating Scale (BPRS), were recorded. RevMan 5.3 was used for the meta-analysis.Results: A total of six randomized controlled trials (174 patients) were included. The overall quality of the included studies was good. No statistically significant benefit of sodium nitroprusside over placebo was found when combined PANSS total and BPRS-18 (95% CI: -1.40, 0.02). Except for PANSS positive (95% CI: -1.86, -0.01), there was no significant difference in the scale score after sodium nitroprusside treatment compared with the control group in PANSS total (95% CI: -4.93, 0.23), PANSS general (95% CI: -2.53, 1.33), and PANSS negative (95% CI: -4.44, 0.89). The results of the sensitivity analysis excluding the study with clinical heterogeneity showed that sodium nitroprusside had no statistical benefit for the score of PANSS positive (95% CI: -2.19, 0.46). Moreover, there was also no significant difference in the BPRS-18 (95% CI: -3.23, -0.43).We conservatively believe that sodium nitroprusside does not alleviate the symptoms of schizophrenia compared with placebo. The subjects tolerated sodium nitroprusside well. Our findings provide a new idea for researchers to explore and solve the drug treatment of schizophrenia.